Mitochondrial uncoupling protein gene cluster variation (UCP2–UCP3) and the risk of incident type 2 diabetes mellitus: The Women's Genome Health Study - Zee, Robert Y.L.; Ridker, Paul M; Chasman, Daniel I. (Atherosclerosis, 2011)
Uncoupling protein 2, mitochondrial, (UCP2) gene variation has recently been implicated in type 2 diabetes mellitus (T2DM). To date, no prospective epidemiological data are available. The association between 14 UCP (UCP2–UCP3) gene cluster tagging-SNPs and incident T2DM was investigated in 22,715 Caucasian participants of the prospective Women's Genome Health Study. All were free of known cardiovascular disease and diabetes at baseline. During a 13-year follow-up period, 1445 participants developed an incident T2DM. Multivariable Cox regression analysis was performed to investigate the relationship between genotypes and T2DM risk assuming an additive model. Stratified analysis by smoking status, and haplotype analysis were also performed. No evidence for an association of any of the tagging-SNPs tested with T2DM risk. Further investigation using stratified analysis, and haplotype-based approach showed similar null findings. The present investigation suggests that the UCP gene cluster variation may not be useful predictor for T2DM risk assessment.